2000
DOI: 10.1103/physrevlett.84.991
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Anisotropy of Upper Critical Field inSr2RuO4

Abstract: We investigated the behavior of the spin-triplet superconductor Sr2RuO4 ( T(c) approximately 1.5 K) under the magnetic fields parallel to the quasi-two-dimensional plane. The upper critical field H(c2) exhibits a clear fourfold anisotropy of about 3% at 0.35 K. Furthermore, we detected an additional transition feature below H(c2) in both the ac susceptibility and the specific heat. These second-transition features as well as the pronounced in-plane H(c2) anisotropy disappear above 0.8 K or under intentional fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
105
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 18 publications
13
105
4
Order By: Relevance
“…Intriguingly, this analysis also points to the possibility of a tetra-critical point in the H-T phase diagram. This tetracritical point has features that agree with recent experimental measurements in high magnetic fields 14 . Given the difficulties that the chiral p-wave state has explaining the H-T phase diagram, we also address the possibility of an in-plane d-vector to see if it can account for the observed phase diagram.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Intriguingly, this analysis also points to the possibility of a tetra-critical point in the H-T phase diagram. This tetracritical point has features that agree with recent experimental measurements in high magnetic fields 14 . Given the difficulties that the chiral p-wave state has explaining the H-T phase diagram, we also address the possibility of an in-plane d-vector to see if it can account for the observed phase diagram.…”
Section: Introductionsupporting
confidence: 81%
“…While there has been no evidence of multiple superconducting transitions in the low-field regime, two superconducting transitions have been observed in the high-field range 14,44 . In one aspect these transitions are natural candidates for two transitions discussed above.…”
Section: Tetracritical Pointmentioning
confidence: 98%
See 1 more Smart Citation
“…Using an ingenious 17 O NMR analysis, Takashi Imai and his coworkers separated the contributions of the a,b and g sheets to the susceptibility and found that the spin susceptibility was more strongly enhanced on the g sheets. 10 Imai's result implies that, when the temperature drops below T c , superconductivity initially appears in this sheet.…”
Section: Multi-orbital Effectsmentioning
confidence: 99%
“…The first NMR test came from Kenji Ishida and his coworkers, who found that the 17 O Knight shift was totally unaffected by the transition into the superconducting state 7 (see figure 3). Note, however, that the spin-orbit interaction blurs the distinction between spin-singlet and spin-triplet pairing.…”
Section: Evidence For Spin-triplet Pairingmentioning
confidence: 99%